Sosialisasi Bencana dengan Model Problem Based Learning Berbantuan Media Visual Sebagai Mitigasi Bencana Bagi Peserta Didik - Istiqamah Istiqamah; Suwarno Suwarno (UM Purwokerto Press, 2022)
Indonesia is a disaster-prone country because it is located in the world's ring of fire and the confluence of three plates so that students as part of the community need to have disaster knowledge as a disaster mitigation effort. Disaster socialization can be done through classroom learning activities. This research uses a descriptive qualitative approach with a literature study method. The purpose of this study is to describe and explain the concept of understanding disaster socialization and disaster socialization steps with the Problem Based Learning model assisted by visual media. Data collection techniques with documents in the form of scientific articles, books, pictures, and news from the media. Data analysis went through three stages, namely data reduction, data display and conclusion drawing/verification. The results of the research are 1) disaster socialization can be interpreted as an effort to convey information about disasters and disaster education to the community, so that people can recognize, understand and live it, 2) disaster socialization through the Problem Based Learning model assisted by visual media is carried out by the following steps: determine basic competencies and learning objectives, determine the time of socialization, prepare materials, prepare visual media to be used, make Learning Implementation Plans by applying the Problem Based Learning model and implementation of socialization. By raising the problem of disaster related to the environment of students as a real problem in the Problem Based Learning Model, it is hoped that it can raise awareness in students about the potential for disasters that can occur in their area. By the knowledge and skills of disaster possessed, students can be responsive and alert in dealing with situations.